BIO SOCIAL RISK FACTORS OF ACUTE STROKE: A CASE CONTROL STUDY FROM TERTIARY CARE HOSPITAL OF UTTARAKHAND - Dr. Yogesh Saxena; Dr. Manish Mittal; Dr. Malini Shrivastava; Dr. Shailendra Raghuvanshi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background & objectives: Stroke is third most common cause of death worldwide. It represents 1.2% of the total deaths in India. Various research findings from the state of Uttarakhand shows high prevalence of alcoholism, tobacco addiction, Hypertension etc. making the population prone for stroke. With the objective of identifying the risk factors for development of stroke present case - control study was carried out in a tertiary care hospital. Methods: 200 diagnosed patients of stroke were included in the study. For each case, one control without clinical athero-thrombotic disease, matched for age, sex and geographical residence area was selected. Various risk factors like hypertension, diabetes, addiction habits, stress profile, etc were studied by standard procedures. Results: Isolated hypertension (OR=27.5), Stress (OR=10.5), History of Diabetes Mellitus with Hypertension( OR=6.51), Daily smoking(OR=3.01), were found as important risk factors .Result showed a very interesting pattern of risk factor prevalence in agewise analysis. Amongst younger age group (20-40 years) Stress (OR-7.33), Daily smoking (OR-4.45) and Hypertension (OR- 4.41) were found to be major risk factors. With the advancement of age during 40-60 years- stress (OR-24.2) remains the major risk factor while Hypertension (OR- 11.2), takes over the Daily smoking habit (OR-2.62). With reaching elderly age( >60 years age) hypertension (OR- 19.14)becomes the stronger risk factor followed by habit of Daily smoking (OR-6.02). Interpretation & conclusions.: Major risk factor in this set of population is Stress followed by Hypertension and smoking. Preventive strategies must investigate causes of stress and its management techniques as primordial and primary prevention besides other risk factors.